George W. Wallace correspondence - Wallace, George W.
ALS written by Wallace to Earl Van Dorn relating to transportation between military posts in Texas.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Van Dorn, Earl, -- 1820-1863 -- Correspondence; United States. -- Army -- History -- 19th century; Military bases -- Texas; Transportation, Military -- Texas; Army officers